Effect of hydraulic properties of soil on rainfall-induced slope failure - Rahimi, Arezoo (2011)
Rainfall-induced slope failure is a common occurrence in many parts of the world. Particularly in tropical regions which are covered extensively with residual soils, the temporal frequency of rainfall-induced slope failure is very high. Hydraulic properties of soil as defined by soil–water characteristic curve, saturated coefficient of permeability and unsaturated permeability function are essential properties that affect rainfall-induced slope failures. The effects of hydraulic properties of soil on rainfall-induced slope failure are investigated through a series of parametric studies. The results of the parametric studies show that soil–water characteristic curve fitting parameters affect the stability of poor drainage soil slopes more significantly than the stability of good drainage soil slopes. The stability of good drainage soil slopes is not sensitive to the variation of soil–water characteristic curve fitting parameters. The saturated coefficient of permeability, ks, of soil has a unique effect on the stability of both good and poor drainage soil slopes.